NETNOGRAPHIC STEREOTYPES OF MUSLIM WOMEN ON INSTAGRAM: A GENDER DYNAMICS IN COMEDY CONTENT - Muhammad Tahir; Riska Dwi Agustin (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2023)
This study attempts to analyze the gender stereotypes embedded in Muslim women as the subject of jokes and blasphemy on Instagram. These stereotypes generally lead to the image of Muslims as arrogant, selfish, troublemakers, and stupid. The study uses a netnographic approach, in which data is obtained through observations of comedy content on Instagram, then analyzed using interactive data models analyzed by Miles, Hubermann, and Saldana. The results of this study found that the stereotype of Muslim women in the virtual space is formed by a gender-biased social construction in the field of fact. This construction was used by content creators as a material to design Instagram content full of jokes and gossip about women. Even the emergence of such stereotypes is driven by the economic motives of the “owners” of the account. It is from here that there is a need to strengthen the self-awareness of content creators in self-imagining and representing women. An egalitarian and non-gender consciousness, both factual and virtual.